Physical and Chemical Study of Manalagi Apple Peel (Malus sylvestris) Kombucha on 7 Days Fermentation Time: Studi Fisik dan Kimia Kombucha Kulit Apel Manalagi (Malus sylvestris) dengan Waktu Fermentasi 7 hari - Kinanti Ayu Puji Lestari; Floreta Fiska Yuliarni; Widya Dara Anindya (Akademi Farmasi Surabaya, 2023)
KKombucha was one of the millennial beverage with a lot of benefits. Kombucha was a subject of research that was always interesting to discuss because of the various indicators of its subject. One of them was the Manalagi apple peel kombucha which was very rare on reviewed. This research focuses on the physical and chemical aspects of Manalagi apple peel kombucha. Manalagi apple peel kombucha is made in three different formulations namely FKA, FKB and FKC and fermented for 7 days. Each kombucha then went through a physical test which included thickness, wet weight, dry weight, moisture content and chemical evaluation as seen from changes in the pH of the kombucha using universal pH paper. The results showed that the physical evaluation of Manalagi apple peel kombucha with the FKC formulation had the highest thickness, wet weight, dry weight and yield, while the FKB formulation had the highest water content. While the pH of each formulation of kombucha apple skin Manalagi decreased and there were differences in values on the surface, middle and bottom of each formulation from pH 5 to pH 4 and 3.